Bandits, Bondsmen, and Leviathans: Ethnic Groups Contesting Local Security After Conflict In the Western Balkans - Jackson, Christopher (Journal of Regional Security, 2021)
This study analyzes how processes of contesting ethnically-distinct locales after conflict affect stability and violence after institutional settlements. Local institutions that develop during conflict present an obstacle to states reestablishing a monopoly on force and these locales become sites of continued contestation. Where states attempt to crowd local institutions and elites out of post-conflict policing, they have incentives to use violence against the state and police to upset the status quo. Where local institutions are integrated into state institutions, local elites have the incentive to maintain order and prevent violence to avoid crowding out or inviting police operations by interveners. In this study, I combine rationalist modelling to generate expectations for local elites’ behavior with three illustrative case studies from the Western Balkans: Kosovo, Macedonia, and southern Serbia.